2016
DOI: 10.1104/pp.16.00256
|View full text |Cite
|
Sign up to set email alerts
|

The bZIP protein VIP1 is involved in touch responses in Arabidopsis roots

Abstract: VIP1 is a bZIP transcription factor in Arabidopsis (Arabidopsis thaliana). VIP1 transiently accumulates in the nucleus when cells are exposed to hypoosmotic conditions, but its physiological relevance is unclear. This is possibly because Arabidopsis has approximately 10 close homologs of VIP1 and they function redundantly. To examine their physiological roles, transgenic plants overexpressing a repression domain-fused form of VIP1 (VIP1-SRDXox plants), in which the gene activation mediated by VIP1 is expected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(61 citation statements)
references
References 61 publications
(63 reference statements)
4
57
0
Order By: Relevance
“…To see whether other genes also exhibit variable expression similarly to mCitrine-ATML1 in the developing sepal nuclei, we measured the expression of two fluorescently-tagged transcription factors, VIP1-mCitrine ( pVIP1::VIP1-mCitrine ) and AP2-2XYpet ( pAP2::AP2-2XYpet ), and the SEC24A transcriptional reporter ( pSEC24A::H2B-GFP ). VIP1 is a mechano-sensitive transcription factor that localizes to the nucleus upon hypo-osmotic treatment (Tian et al, 2004; Tsugama et al, 2016) and AP2 is a master regulator of floral organ identity that is expressed in sepals (Wollmann et al, 2010). SEC24A is a ubiquitously expressed CopII vesicle-coat protein that is involved in vesicle trafficking from the ER to the Golgi and has been previously reported to influence giant cell formation on the sepal (Qu et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To see whether other genes also exhibit variable expression similarly to mCitrine-ATML1 in the developing sepal nuclei, we measured the expression of two fluorescently-tagged transcription factors, VIP1-mCitrine ( pVIP1::VIP1-mCitrine ) and AP2-2XYpet ( pAP2::AP2-2XYpet ), and the SEC24A transcriptional reporter ( pSEC24A::H2B-GFP ). VIP1 is a mechano-sensitive transcription factor that localizes to the nucleus upon hypo-osmotic treatment (Tian et al, 2004; Tsugama et al, 2016) and AP2 is a master regulator of floral organ identity that is expressed in sepals (Wollmann et al, 2010). SEC24A is a ubiquitously expressed CopII vesicle-coat protein that is involved in vesicle trafficking from the ER to the Golgi and has been previously reported to influence giant cell formation on the sepal (Qu et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The mCitrine marker was excited with a 514 nm laser and collected with a 519–564 filter. VIP1 is a bZIP transcripton factor that is cytoplasmically localized under stable conditions but will become nuclear localized upon hypoosmotic treatment (Tsugama et al, 2016). To nuclear localize VIP1, VIP1-mCitrine inflorescences were submerged in a hypoosmotic solution (H2O and 0.001% triton-X) for approximately 10 min prior to confocal imaging.…”
Section: Methodsmentioning
confidence: 99%
“…The proposed involvement of the Arabidopsis bZIP protein VIP1 in Agrobacterium infection is consistent with its known roles in different types of biotic and abiotic stress (Djamei et al ., ; Pitzschke et al ., ; Tsugama et al ., ). Yet, a recent study has suggested that a loss‐of‐function mutant of VIP1 is still susceptible to infection (Shi et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…However, specific VirE2 proteins showed different, yet overlapping, specificities towards individual VIP1 homologues, potentially affecting the host range of the different bacterial species. This subset of VIP1 homologues shares somewhat redundant biological functions in uninfected cells (Tsugama et al, 2014(Tsugama et al, , 2016Van Leene et al, 2016), which suggests that this redundancy could also apply to their interactions with VirE2 during the infection process. Whereas, in nature, the host range of Agrobacterium is essentially limited to dicotyledonous plants, under laboratory conditions, many more eukaryotic species can be transformed by Agrobacterium, from monocotyledonous plants, to yeast and other fungi, to mammalian cultured cells (Lacroix et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation